2021
DOI: 10.3390/agronomy11010116
|View full text |Cite
|
Sign up to set email alerts
|

Selection of New Late-Season Mandarin Cultivars Based on Sensory Changes and Consumer Acceptance after Fruit Cold Storage

Abstract: Late-season mandarins are normally cold-stored to prolong the commercial season. Thus, it is necessary to investigate poststorage consumer acceptance to predict the potential success of new late-season mandarin varieties on the market. The aim of the present work was to evaluate consumer response to three new late-season cultivars preselected in the IVIA breeding programme (Omet, Matiz and Tri-703) after different cold storage periods. The three new cultivars were compared to commercial cultivars Orri, Nadorco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Recently, Tarancón et al [ 4 ] confirmed the negative impact of skin damage on consumer preferences previously described by Campbell et al [ 7 ]. In the aforementioned study [ 4 ], skin disorders associated with chilling injury manifestation during cold storage led to a significant decrease in consumer preferences and purchase intention in relation to harvest time.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…Recently, Tarancón et al [ 4 ] confirmed the negative impact of skin damage on consumer preferences previously described by Campbell et al [ 7 ]. In the aforementioned study [ 4 ], skin disorders associated with chilling injury manifestation during cold storage led to a significant decrease in consumer preferences and purchase intention in relation to harvest time.…”
Section: Introductionsupporting
confidence: 54%
“…Recently, Tarancón et al [ 4 ] confirmed the negative impact of skin damage on consumer preferences previously described by Campbell et al [ 7 ]. In the aforementioned study [ 4 ], skin disorders associated with chilling injury manifestation during cold storage led to a significant decrease in consumer preferences and purchase intention in relation to harvest time. However, other mandarin appearance characteristics linked with postharvest handling are likely to affect the consumer perception of quality, but have not yet been evaluated in this regard.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…One of the reasons for their good position in markets has been breeding seedless and easy-to-peel [3,4]. Thus, breeding programmes have been key for mandarin success in markets by providing the consumer with more convenient fruit of high sensory quality [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, including an IP description in this quite novel methodology of CATA questions has never been used during the process of evaluating new varieties. Based on our expertise in breeding [25,26] and new variety evaluations [8,20,27], we believe that it would be very useful to include this procedure in breeding programs.…”
Section: Introductionmentioning
confidence: 99%